TAX PAYER COMPLIANCE OF TWO-WHEEL VEHICLE OWNERS BASED ON EDUCATION AND WORK TYPE - Rachmat Hidayat; Mirna Dianita; Irene Sukma Lestari Barus; Rudy Lizwaril; Rima Rachmawati; Andry Arifian Rachman (Jurnal Ekonomi, 2023)
The study aimed to determine the effect of level of education, type of work, and the interaction (joint effect) of education and employment on taxpayer compliance Researchers conducted semi-structured interviews. with 100 Bandung residents who work or do business in the districts: Cibeunying Kidul, Cibenying Kaler, and Kiaracondong. The interview guide consists of educational statements and work compliance. Education and work are the independent variables and the dependent variable is compliance. Data analysis using two-way ANOVA Research results: High school education (31), D3 (25), S1 (44), online motorcycle taxi driver jobs (62), MSME (24), and civil servants (14). Respondents were dominated by undergraduate education (44%) and motorcycle taxi drivers (62%). S1 Education has the most influence on compliance. The average adherence to SMA and D3 education is not different, but The average S1 compliance is different from SMA and D3. The average compliance of MSME workers and OJOL drivers is not different, but the average PNS compliance is different from that of MSMEs and online motorcycle taxi drivers. There is an interaction between education and work on compliance.